Effect of light on persistence of imidacloprid in soil - Elzorgani, Mohammed G.A. (International Journal of Advanced Chemistry, 2018)
Imidacloprid are Applied Widely to Protect Crops from Damage by Insect Pest, the Residue Usually Come Into Contact with Soil, where They Undergo A Transformations That Lead to Formation of A Complex Pattern of Metabolites. This Study Was Performed to Study The Persistence And Degradation Of Imidacloprid In Gezira-Sudan Soil As Affected By UV And Sunlight Exposure.The High-Performance Liquid Chromatography (HPLC-DAD) Were Used To Characterize The Photodegradation Kinetics Under The Experiment Condition And To Identify The Main Photoproducts IMI-Urea In Soil Samples As To Propose Plausible Photodegradation Pathways Of Imidacloprid In Soil.Samples Of Soil Were Placed In Petri-Plate, Brought To Field Capacity Moisture And Then Exposed To UV And Sunlight. Residues Of Imidacloprid In Soil Dissipated With Half-Life Of 15.84 Under UV And 60.2 Days Under Sunlight. Exposure Of Thin Film Of Imidacloprid To UV And Sunlight Confirmed That It Is Photo Labile And Dissipated Very Fast With Half-Life 15.05 And 8.6 Days Under UV And Sunlight, Respectively. The Formation Of Imidacloprid-Urea As Main Photoproduct Was Only Detected On Day 7 In The Case Of Thin-Film Exposed To UV-Light. The Study Revealed That UV Component Of Sunlight Is An Important Factor For Imidacloprid Dissipation From Soil Surface.